2023
DOI: 10.1098/rspb.2023.1327
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis precedes apoptosis to facilitate specific death signalling by fatty acids

Valerio Zupo,
Maria Costantini,
Eliahu D. Aflalo
et al.

Abstract: Cell death is physiologically induced by specific mediators. However, our power to trigger the process in selected cells is quite limited. The protandric shrimp Hippolyte inermis offers a possible answer. Here, we analyse a de novo transcriptome of shrimp post-larvae fed on diatoms. The sex ratio of diatom-fed shrimps versus shrimps fed on control diets was dramatically altered, demonstrating the disruption of the androgenic gland, and their transcriptome revealed key modifications in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…This change is a consequence of a programmed cell-death (PCD) trigger directed selectively towards AG cells [ 24 , 25 ]. The chemical structure of the bioactive compound is still under investigation, but it is known to be a small lipophilic compound [ 26 ], probably similar to dihomo-γ-linolenic acid (DGLA) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This change is a consequence of a programmed cell-death (PCD) trigger directed selectively towards AG cells [ 24 , 25 ]. The chemical structure of the bioactive compound is still under investigation, but it is known to be a small lipophilic compound [ 26 ], probably similar to dihomo-γ-linolenic acid (DGLA) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular tools for H. inermis are, at present, very scarce, but Levy et al [ 30 ] have obtained transcriptomic libraries of representative development stages (immature, male, young female and mature female). However, previous studies [ 27 ] revealed a set of genes influenced by the ingestion of diatoms, demonstrating the remarkable role of ferroptosis as a form of PCD specifically acting on still undifferentiated gland tissues. This mechanism appears to be a smart physiologic strategy to produce massive changes in the physiology of an invertebrate by targeting a few young cells, and it has been demonstrated to be evolutionarily conserved, from Caenorabditis elegans to humans [ 27 ] and, of course, is present in the model shrimp H. inermis .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations